Anatomy of the global food crisis - Conceicao, Pedro (Archīum Ateneo, 2009)
Dramatic food price increases affected much of the developing world in 2008. Even as food prices have begun to relax in 2009, this trend is highly uneven across countries, and in many countries local food prices remain high relative to past levels. Furthermore, the challenge of addressing the root causes of the global food crisis remains. This paper contributes to the policy discussions in this area by offering a preliminary diagnostic of the possible factors behind the global food crisis that erupted in 2008. Some are more immediate and possibly short-term in nature, such as the volatility in the commodities markets arising from short-term financial speculation. Others, however, are going to or have already started to affect countries' food security in the medium to longer term. These include rising and changing patterns of consumption in fast-growing and large developing countries like China and India, the possibly increasing trade-off between biofuels and food, and the unfolding effects of climate change. Keeping in mind the possible structural features of the global food landscape from here on, the paper outlines a framework for policy actions, both unilateral and collective, to address the food crisis and ensure future global food security.